The potential of Trichoderma sp. as antibacterial and immunostimulant on white shrimp (Litopenaeus vannamei) - Catur A. Pebrianto; . Sukenda; . Widanarni (Jurnal Akuakultur Indonesia)
The objective of this research was to study antibacterial and immunostimulatory effects of Trichoderma sp. extract on white shrimp, Litopenaeus vannamei.  First experiment was conducted to evaluate inhibitory effect of Trichoderma sp. againts Vibrio harveyi, a pathogenic bacteria causing vibriosis disease on shrimp.  Second experiment was conducted to evaluate immunostimulatory effect of Trichoderma sp. on shrimp immunity as well as protective effect against V. harveyi. A group of shrimp was injected with a minimum inhibitory concentration obtained at first experiment, and a week after, shrimps was challenged with V. harveyi (prophylactic). Another group was previously challenged with V. harveyi, and subsequently injected with Trichoderma sp. two fold of Minimum Inhibitory Concentration (MIC) a day after (therapeutic). Positive control, that was received only V. harveyi, and negative controls, that was received neither Trichoderma sp. nor V. harveyi were included in this experiment.  Results of first experiment showed that a concentration of 600 ppm was a MIC of Trichoderma sp. to inhibit V. harveyi. While in the second experiment, the groups receiving Trichoderma sp., either prophylactic or therapeutic, showed protective effect against V. harveyi significantly higher than positive control and lower compared with negative control. Total haemocyte count (THC), differential haemocyte count (DHC), phagocytic index and phenoloxydase activity were different among the groups of prophylactic treatment or therapeutic treatment compared to control positive and negative treatments. In conclusion, Trichoderma sp. could be used in prophylactic and therapeutic treatments to combat infection of V. harveyi on L. vannamei.